Formal perspectives of Romance linguistics : selected papers from the 28th Linguistic Symposium on Romance Languages (LSRL XXVIII) : University Park, 16-19 April 1998 - Authier, J.-Marc; Bullock, Barbara E.; Reed, Lisa A., 1963- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 1999)
This volume presents current research in the formal treatment of linguistic phenomena in the Romance languages. It focuses on a variety of issues in phonology, second language acquisition, semantics, and syntax. Topics in phonological theory include the analysis of geminates, assimilation, rhotics, aspiration, syllabification, the interaction of phonology with morphology, the phonology-phonetics interface, and issues of transderivation and allomorphy selection. The primary question addressed in the area of second language acquisition theory is the issue of learners' access to Universal Grammar.